AB1185 Real-life experience and mutual expectations of patients affected with chronical inflammatory rheumatic diseases and their relatives; consequences in patient education: a qualitative study by the proxyric group of the patient education division of french rheumatic disease society. (15th June 2017) - Poivret, D; Untas, A; Boujut, E; Vioulac, C; Delannoy, C; Carton, L; Legoupil, N; Hayem, G; Pouplin, S; Rat, A-C; Quintrec, J-S Giraudet-Le; Beauvais, C
Abstract : Background: Interaction with relatives has a significant role on patients' health, and can also impair relatives'health. Education processes need codification to enrole relatives in the programms. Objectives: To create a patient education program for relatives and patient affected by rheumatic inflammatory desease Methods: Individual semi-directed by 2 psychologists interviews, have been performed and their thematic content analysed with the QDA Miner program. A guide had been achieved by rheumatologists, psychologists et patient association representatives. The (patient/relative) dyad, has been first questioned together, and then individually. Results: 20 patients, average age 59 years (27–79) affected with Rheumatoïd Arhritis (n=13), Spondyloarthritis (n=9) with an average disease duration of 12, 8 years (1–39) and one of their relatives (being their spouse in 18 cases) have been recruited in 7 rheumatology departments in France. Common life duration was 27, 5 years as an average (1, 5–57). About 2/3 of patients and relatives have a common view on: relative's role in bringing an emotional support but needs a knowledge on disease and treatments; emotional distress experienced by both patient and relative; the worrries and reative's feelings of not knowing how to to do; the help brought by the relative in everyday's life and his participation to care management. Only a few relatives talked about concerns, regrets of past life, and burden feeling of patient. Relatives also express unfairness feelings. 2/3 of patients and relatives report will of independence of the patient, who wants to manage alone, and does not express his difficulties. 50% of relatives think they anticipate patient's needs, they are also directly resquested by the patients. On the other side, the patients often report that they watch over relative's health. 50% of patients and relatives mention the idea of complementarity and " team ", but also tensions or conflicts. Patient Education contribution would be sharing and exchanging between them, according to 2/3 of patients and relatives, who therefore would prefer group education (12/20). Relatives however more often mention a common education with patient, and patients prefer a separate education of relative. The main limit to of this study is that participation to study has favored harmoniously functioning dyads, what may explain the weak rate of abandonment feeling. Conclusions: Expectations on relatives' role seem to be common in terms of practical and emotional support. Relatives sometimes mention the "positivation" of their role, but also emotional distress and helplessness feeling. Patients fear they are a burden and want to be independent. A specific educational management of relatives is more often suggested by patients than by relatives. Disclosure of Interest: None declared